STATISTICAL ANALYSIS OF THE LEVEL OF WAGES IN THE EDUCATION SECTOR OF UKRAINE AND ASSESSMENT OF PROSPECTS FOR ITS INCREASE - GITIS, Tetiana; PIDHORA, Yelyzaveta (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The aim of the study is to identify the main trends in changes in the level of wages in the education sector of Ukraine and to assess the prospects for its increase using statistical analysis methods. A generalised indicator of the level of wages is the average monthly nominal wage of regular employees by type of economic activity – Education.In the course of analysing the dynamics of the average monthly nominal wage of employees in the Ukrainian education sector in 2010-2023, the following was determined: the level of salaries in education is significantly lower than the average for the economy and gradually approaching the minimum wage; the growth rate of wages has been slowing down in recent years and is relatively low on average. It has been determined that the dynamics of the level of wages of employees in the educational sector of Ukraine is quite sensitive to changes in the minimum wage. A regression model, which has been formed, reflects the analytical form of the relationship between the growth rate of the average monthly nominal wage in the education sector of Ukraine (the resultant variable) and the growth rate of the average minimum wage (the factor variable). The projected dynamics of the average monthly nominal wage in education shows a slowdown in its growth rate in 2025-2026, provided that the minimum wage is frozen at the level of 2024 (according to the budget declaration for 2025-2027). Considering the planned increase in consumer prices in the budget declaration, a significant reduction in real wages in the education sector is forecasted.The results of the analysis show that labour in the education sector is low-paid and that no significant increase in wages is expected in the coming years. This situation may lead to a significant shortage of qualified personnel, which will negatively affect the quality of educational services.
Keywords: education sector; average monthly nominal wage; growth rate; minimum wage; regression model